Pelvic tuberculosis: from millets to masses - Shah, Nitin H; Joshi, Aditi Vivek; Mourya, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
An adnexal mass is a common entity in the reproductive age group. Ovarian masses form a majority of this condition. Tuberculosis is a disease commonly encountered in the Tropics and is endemic to India. Abdominopelvic affliction of this disease is common in women especially in the reproductive age groups. It may present with variety of non-specific clinical features and often poses an enormous diagnostic dilemma Author report one such case, presenting with a clinical impression of ovarian malignancy, however, was diagnosed to be a case of extensive pelvic tuberculosis on laparoscopy. Tissue biopsy was consistent with the finding of tuberculosis.